2009
DOI: 10.1080/02642060903026262
|View full text |Cite
|
Sign up to set email alerts
|

The important effect of employee's emotion management ability on his/her service behaviour in the international tourist hotel

Abstract: The main purpose of this study is to clarify the relationship between the employee's emotion management and service behaviour by analysing employees in the international tourist hotel, which involves high degrees of emotional labour that is more complex than in other industries. According to the empirical evidence, the ability of selfemotional appraisal and other's emotional appraisal become the important factors for in-role cooperative service behaviour and extra-role service behaviour. The practices can rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 32 publications
1
16
0
3
Order By: Relevance
“…Consequently, the working conditions within the hospitality industry make it impossible for employees to benefit from satisfactory levels of psychological needs, such as an increase in psychological well-being and a proper work-life balance (Haider et al, 2018). However, the quality of the employee-customer relationship is crucial (Castellanos-Verdugo et al, 2009), particularly in the hospitality industry, in which service employees are among the most relevant success factors (Tsai, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the working conditions within the hospitality industry make it impossible for employees to benefit from satisfactory levels of psychological needs, such as an increase in psychological well-being and a proper work-life balance (Haider et al, 2018). However, the quality of the employee-customer relationship is crucial (Castellanos-Verdugo et al, 2009), particularly in the hospitality industry, in which service employees are among the most relevant success factors (Tsai, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Since technology use is inevitable in hotel industry, hotel managers are concerned about how Internet use can bring in more customers. Review of the literature suggested that job satisfaction of employees and employers, organizational commitment, customer loyalty, and brand image have been a focus of research [3][4][5][6]. How hotel online reservation system affects consumer decision-making process when choosing a hotel has not been addressed much in prior research.…”
Section: Introductionmentioning
confidence: 99%
“…Bu yüzden duygusal emek sergileyerek iş gereklerini yerine getirmektedirler. Özellikle otelcilik sektöründe, hizmet sürecinde zorlayıcı etkileşimler fazlaca yer aldığından (Cugini, Caru ve Zerbini, 2007;Tsai, 2009) iş ve aile yaşamında çatışmaların ortaya çıkması da kaçınılmazdır.…”
Section: İş-aile Ve Aile-i̇ş çAtışmasında Duygusal Emeğin Etkisiunclassified
“…So, they perform their job requirements by exhibiting emotional labor. It is inevitable that conflicts will occur in work and family life, especially in the hotel sector, as the compelling interactions in the service process take up (Cugini et al, 2007;Tsai, 2009) too much .…”
Section: Extended Abstractmentioning
confidence: 99%